Effects of Computerized Interventions on Risky Alcohol Use Among Youth: Systematic Review. (October 2019) - Smedslund, Geir; Nilsen, Wendy; Wollscheid, Sabine; Steiro, Asbjørn; Fang, Lin; Larun, Lillebeth
Purpose: The study assessed the effectiveness of computerized brief interventions (CBIs) for youth (aged 15–25) defined as risky alcohol users. Methods: We searched 10 electronic databases. Eligible studies were randomized and quasi-randomized controlled trials examining the effect of CBIs for youth. Results: Fifty-three studies with 33, 316 participants were included. Moderate quality evidence showed CBIs to reduce risky alcohol use compared to single-dose assessment. Short-term (<6 months) effects were overall larger than long-term (≥6 months) effects. None of the studies reported adverse effects. Conclusions: The positive effects, easy administration, and lack of adverse effects of CBIs indicate that such brief interventions are a feasible way to reduce risky alcohol use in youth.